MEMBACA LUKISAN AGUS SUWAGE:`THE SUPER OMNIVORE` - Lilik Indrawati (Bahasa dan Seni: Jurnal Bahasa, Sastra, Seni, dan Pengajarannya, 2012)
Appreciating the Indonesian contemporary  work of painting created by Agus Suwage must be related to the painter’s birth, existence, culture, and the nation environments condition. Mostly, Suwage exploit himself as an object which later on becomes a medium to express his restlessness through his ideas . The object of self portrait  in  Suwage’s  painting  is  a  metaphoric  icon.  However,  the  portraiture technique which is chosen by Suwage in his paintings does not tell a story about himself.